DISKRIMINASI HARGA BERBASIS GENDER (PINK TAX) : PELANGGARAN UNDANG-UNDANG PERLINDUNGAN KONSUMEN - Yustisha, Ammi (UNES Law Review, 2023)
The practice of gender-based price discrimination is known as the "Pink Tax". The "Pink Tax" phenomenon reflects an unfair price gap (discrimination) based on the gender of consumers. Gender-based price discrimination not only harms female consumers financially, but also reflects unfairness and inequality in the market. Consumer protection plays an important role in safeguarding the rights and interests of consumers from harmful practices. This research focuses on analyzing whether the practice of gender-based price discrimination (pink tax) is a violation of consumer protection laws in Indonesia? This research uses normative juridical research methods by analyzing the positive law governing consumer protection in Indonesia, namely Law Number 8 of 1999 concerning Consumer Protection (UUPK). Although the UUPK has accommodated efforts to protect consumers from discriminatory behavior of business actors, unfortunately the term "discriminatory" is only limited to regulating discriminatory treatment based on ethnicity, religion, culture, region, education, rich, poor and other social status, not including discriminatory treatment based on sex/gender. So it can be concluded that the practice of gender-based price discrimination (pink tax) in Indonesia cannot be categorized as a violation of Law Number 8 of 1999 concerning Consumer Protection.